2010
DOI: 10.1002/ptr.3079
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl acetate fraction of the root of rubia cordifolia L. inhibits keratinocyte proliferation in vitro and promotes keratinocyte differentiation in vivo: potential application for psoriasis treatment

Abstract: Psoriasis is a skin disease associated with hyperproliferation and aberrant differentiation of keratinocytes. Our previous studies have identified the root of Rubia cordifolia L. as a potent antiproliferative and apoptogenic agent in cultured HaCaT cells (IC(50) 1.4 microg/ml). In the present study, ethanolic extract of Radix Rubiae was fractioned sequentially with hexane, ethyl acetate (EA), n-butanol and water. EA fraction was found to possess most potent antiproliferative action on HaCaT cells (IC(50) 0.9 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…These roots are usually used to treat inflammation of the joints, dysmenorrhea, hematorrhea, hemostasis, and psoriasis. 5,6) Mollugin, the major and index component determining the quality of Rubia cordifolia L., was reported to have several pharmacological effects, such as cytotoxic and anti-tumor activities, 7) anti-platelet aggregation activity, 8) and antiviral activity against hepatitis B virus. 9) Recently, Kim and Jeong reported that mollugin might be a new drug candidate for the treatment of inflammatory diseases, such as colon inflammation and neurodegenerative diseases.…”
mentioning
confidence: 99%
“…These roots are usually used to treat inflammation of the joints, dysmenorrhea, hematorrhea, hemostasis, and psoriasis. 5,6) Mollugin, the major and index component determining the quality of Rubia cordifolia L., was reported to have several pharmacological effects, such as cytotoxic and anti-tumor activities, 7) anti-platelet aggregation activity, 8) and antiviral activity against hepatitis B virus. 9) Recently, Kim and Jeong reported that mollugin might be a new drug candidate for the treatment of inflammatory diseases, such as colon inflammation and neurodegenerative diseases.…”
mentioning
confidence: 99%
“…The antiproliferative activity of CJPE was comparable with that exhibited by the Caesalpinia bonduc (L.) Roxb. hydroalcoholic extract (IC 50 value ¼ 77.5 mg/ml), ethanolic extract of yellow birch obtained by 48 h maceration (IC 50 value ¼ 94.80 mg/ml), and was better than black spruce extract obtained by hot water extraction (IC 50 value ¼ 94.80 mg/ml); however, it possessed less activity than the root extract of R. cordifolia (IC 50 value ¼ 1.4 mg/ml), Realgar (IC 50 value ¼ 6.6 mg/ml), and the rhizome of C. chinensis (IC 50 value ¼ 23.4 mg/ml) (Lin et al, 2010;Prepare et al, 1995;Tan et al, 2011;Tse et al, 2006;Zhou et al, 2012).…”
Section: Resultsmentioning
confidence: 89%
“…Its impact on the quality of life is found to be nearly similar to that associated with other chronic medical conditions such as diabetes and depression (Korte et al, 2004;Krueger et al, 2001). (Zingiberaceae), etc., are found to be effective for the treatment of psoriasis (Koo & Arain, 1998;Koo & Desai, 2003;Lin et al, 2010;Prepare et al, 1995;Tan et al, 2011;Tse et al, 2006;Zhou et al, 2012). In this study, four Indian medicinal plants, namely, Phyllanthus simplex Retz.…”
Section: Introductionmentioning
confidence: 73%
“…In BALB/c mice, the effect of a R. cordifolia extract-containing gel was evaluated after 4 weeks of application on the mouse tails. The gel with 5% R. cordifolia extract significantly increased the thickness of the granular layer and the epidermis as opposed to the vehicle [27] .…”
Section: Rubia Cordifoliamentioning
confidence: 99%
“…An ethyl acetate extract obtained from R. cordifolia roots displayed antiproliferative and apoptosis-inducing effects on HaCaT keratinocytes [27] . In BALB/c mice, the effect of a R. cordifolia extract-containing gel was evaluated after 4 weeks of application on the mouse tails.…”
Section: Rubia Cordifoliamentioning
confidence: 99%